Butler, J. (2020). Sin miedo. Formas de resistencia a la violencia hoy (Trad. Inga Pellisa Díaz) Taurus. ISBN: 978-84-306-2349-5 - Pérez Barreiro, Ana Belén (Cuadernos del CILHA, 2022)
Reseña sobre Butler, J. (2020). Sin miedo. Formas de resistencia a la violencia hoy (Trad. Inga Pellisa Díaz) Taurus. ISBN: 978-84-306-2349-5.